2017
DOI: 10.3390/socsci6030101
|View full text |Cite
|
Sign up to set email alerts
|

The Web of Loneliness: A Netnographic Study of Narratives of Being Alone in an Online Context

Abstract: Using a netnographic and case-study-based approach, this article uses different blogs as data in order to analyse how loneliness is conceptualized and understood. More precisely, the study aims to investigate experiences of loneliness and related themes in the context of online communication. In approaching the nature of loneliness, we have analytically leaned on the theories and some of the most basic assumptions of symbolic interactionism, according to which, social encounters and situations, their qualities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 48 publications
(40 reference statements)
0
7
0
Order By: Relevance
“…Of the total number of articles, 26.4% ( n = 14) reported that their study had been reviewed by an ethics board (Alang & Fomotar, 2015; Andréasson et al, 2018; Aragão et al, 2018; Boursier et al, 2022; Cano-Hila & Argemí-Baldich, 2021; Ellinghaus et al, 2021; Gün & Şenol, 2019; Kendal et al, 2017; Lawless et al, 2020, 2022; Moura & Aschemann-Witzel, 2021; Schuman et al, 2019; Vale et al, 2019; Wallace et al, 2018), while 56.6% ( n = 30) reported that their study had not been reviewed (Ari & Mari, 2021; Baptista et al, 2021; Bayen et al, 2021; Bîră et al, 2020; Björkman & Salzmann-Erikson, 2018; Botelle & Willott, 2020; Cuomo et al, 2020; Eriksson et al, 2014; Eriksson & Salzmann-Erikson, 2013, 2016b, 2018; Gatrell, 2019; Holmgren et al, 2018; Johansson & Andreasson, 2017; Keeling et al, 2015; Liang & Scammon, 2011; Manning Hutson et al, 2022; Nemec et al, 2018; Nimrod, 2011; Numer et al, 2022; Poppi, 2021; Salzmann-Erikson, 2016, 2017; Salzmann-Erikson & Eriksson, 2011; Saxena et al, 2021; Song, 2020; Strand, 2022, p. 202; Strand & Gustafsson, 2020; Thunborg & Salzmann-Erikson, 2017; Van Hout & Hearne, 2014); four articles reported that they had applied to an ethics review board (ERB) but had been deemed exempt because their work was not considered human subjects research (De Gagne et al, 2021; Giles et al, 2015; …”
Section: Resultsmentioning
confidence: 99%
“…Of the total number of articles, 26.4% ( n = 14) reported that their study had been reviewed by an ethics board (Alang & Fomotar, 2015; Andréasson et al, 2018; Aragão et al, 2018; Boursier et al, 2022; Cano-Hila & Argemí-Baldich, 2021; Ellinghaus et al, 2021; Gün & Şenol, 2019; Kendal et al, 2017; Lawless et al, 2020, 2022; Moura & Aschemann-Witzel, 2021; Schuman et al, 2019; Vale et al, 2019; Wallace et al, 2018), while 56.6% ( n = 30) reported that their study had not been reviewed (Ari & Mari, 2021; Baptista et al, 2021; Bayen et al, 2021; Bîră et al, 2020; Björkman & Salzmann-Erikson, 2018; Botelle & Willott, 2020; Cuomo et al, 2020; Eriksson et al, 2014; Eriksson & Salzmann-Erikson, 2013, 2016b, 2018; Gatrell, 2019; Holmgren et al, 2018; Johansson & Andreasson, 2017; Keeling et al, 2015; Liang & Scammon, 2011; Manning Hutson et al, 2022; Nemec et al, 2018; Nimrod, 2011; Numer et al, 2022; Poppi, 2021; Salzmann-Erikson, 2016, 2017; Salzmann-Erikson & Eriksson, 2011; Saxena et al, 2021; Song, 2020; Strand, 2022, p. 202; Strand & Gustafsson, 2020; Thunborg & Salzmann-Erikson, 2017; Van Hout & Hearne, 2014); four articles reported that they had applied to an ethics review board (ERB) but had been deemed exempt because their work was not considered human subjects research (De Gagne et al, 2021; Giles et al, 2015; …”
Section: Resultsmentioning
confidence: 99%
“…In addition, information remains permanently available on the web, allowing users to choose which subjects to access (Camilleri, 2017;Dowling, 2008;du Plessis et al, 2018;Jackson, 2010). In addition to corporate websites, companies exhaust social networking platforms engage with stakeholders through interactive communication (Johansson & Andreasson, 2017;Liu et al, 2017;Tavakoli & Wijesinghe, 2019;Vecchio et al, 2011).…”
Section: Companiesmentioning
confidence: 99%
“…in our cities. Loneliness is largely a social phenomenon and a social form Johansson, T and Andreasson T [27]. (Urban) Loneliness, product of partly (urban or 'agorian') social (and even physical) isolation and retreat and partly our own subjective (metaphysical, subconscious, conscious and synchronicity) interpretation of our lives, can become a public health problem in our cities.…”
Section: Implication For Planning and Urban Design Policy For Combatting (Urban) Loneliness Through Urban Form And Human Behavior Approacmentioning
confidence: 99%